HIV, opioid use, and alterations to the gut microbiome: elucidating independent and synergistic effects - Satish, Sanjana; Abu, Yaa; Gomez, Daniel; Kumar Dutta, Rajib; Roy, Sabita (Frontiers in Immunology, 2023)
Background: The microbiome is essential to immune development, defense against pathogens, and modulation of inflammation. Microbial dysbiosis has been reported in various diseases including HIV and opioid use disorder (OUD). Notably, people living with HIV (PLWH) have been reported to both have higher rates of OUD and use opioids at higher rates than the general public. Thus, studying gut microbial alterations in people living with HIV and with OUD could elucidate mechanisms pertaining to how these conditions both shape and are shaped by the microbiome. However, to date few studies have investigated how HIV and OUD in combination impact the microbiome. Aim of Review: Here, we review previous studies outlining interactions between HIV, opioid use, and microbial dysbiosis and describe attempts to treat this dysbiosis with fecal microbial transplantation, probiotics, and dietary changes. Key Scientific Concepts of Review: While the limited number of studies prevent overgeneralizations; accumulating data suggest that HIV and opioid use together induce distinct alterations in the gut microbiome. Among the three existing preclinical studies of HIV and opioid use, two studies reported a decrease in Lachnospiraceae and Ruminococcaceae, and one study reported a decrease in Muribaculaceae in the combined HIV and opioid group relative to HIV-alone, opioid-alone, or control groups. These bacteria are known to modulate immune function, decrease colonic inflammation, and maintain gut epithelial barrier integrity in healthy individuals. Accordingly, modulation of the gut microbiome to restore gut homeostasis may be attempted to improve both conditions. While mixed results exist regarding treating dysbiosis with microbial restoration in PLWH or in those with opioid dependency, larger well-defined studies that can improve microbial engraftment in hosts hold much promise and should still be explored.